Population genomics fits the bill: genetics of adaptive beak variation in Darwin's finches - Nicholas I. Mundy (Molecular Ecology, 2016)
Darwin's finches are an iconic case of adaptive radiation. The size and shape of their beaks are key adaptive traits related to trophic niche that vary among species and evolve rapidly when the food supply changes. Building on recent studies, a paper in this issue of Molecular Ecology (Chaves et al . ) investigates the genomic basis of beak size variation in sympatric populations of three species of ground finch ( G eospiza ) by performing a Genome‐wide association study using RAD ‐seq data. The authors find that variation in a small number of markers can explain a substantial proportion of variation in beak size. Some of these markers are in genomic regions that have previously been implicated in beak size variation in D arwin's finches, whereas other markers have not, suggesting both conservation and divergence in the genetic basis of morphological evolution. Overall, the study confirms that loci of large effect are involved in beak size variation, which helps to explain the high heritability and rapid response to selection of this trait. The independent identification of regions containing HMGA 2 and DLK 1 loci in a GWAS makes them prime targets for functional studies. The study also shows that under the right conditions, RAD ‐seq can be a viable alternative to genome sequencing for GWAS in wild vertebrate populations.

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)